DESIGNING A WEB-BASED TICKET SALES SYSTEM: CASE STUDY OF TEMESI WATERFALL, GIANYAR BALI - Diana Rahayu; Ni Putu Eka Amaylia Kusuma Dewi; I Gede Yoga Dana Saputra; Ni Kadek Vidya Aishwanari; I Gusti Ngurah Agung Wiryanata; Ni Ketut Mareni; I Dewa Ayu Rai Sumariati (RADJA PUBLIKA, 2025)
Rural tourism destinations in Bali, such as Temesi Waterfall in Temesi Village, Gianyar Regency, possess significant development potential but are constrained by inefficient manual management systems. This study aims to design and implement a web-based ticketing information system to address operational limitations. Utilizing a qualitative descriptive methodology, the research resulted in the development of Postrack, a digital system incorporating features such as transaction management, a digital guestbook, dynamic ticket pricing, financial reporting, expense monitoring, and user activity tracking. Implementation of the system demonstrated improved operational efficiency, enhanced accountability, and increased financial transparency. The findings suggest that digitalization through systems like Postrack can significantly optimize tourism management in rural areas. Furthermore, this model can be replicated across similar destinations to support broader efforts in technology-based rural tourism development and sustainable management practices.